(untitled) (LIS TODAY, 2025)
Engineering, an application of scientific, economic, social, and practical knowledge that designs, builds, maintains structures, machines, devices, systems, materials and processes that plays a key role in socio-economic development of any nation. Excellent engineering colleges are essential to prepare engineers with good knowledge and skills in engineering. The library is a very important source of information and knowledge of any educational organization. Unless these libraries have sufficient resources such as finance, building, furniture etc., they may not be able to provide necessary services to their users. The present paper highlights the need and importance of various E -Resources in selected Engineering College Libraries under study. The main objectives of the present study are to find out the existing e-resources and to study the awareness level and use of e-resources by the users. It further states the satisfaction level of users towards e-resources and finds out users preference in the use of print and e-resources and cause of their preferences. The survey method was used to collect the requisite data for the analysis for which questionnaire was framed and were distributed among the users. About 570 questionnaires were received back duly filled. The study covered the students and faculty members. From the study it was clear that students and faculty members give preferences on e- resources than printed material. In current scenario electronic resources are becoming an essential part of the engineering libraries and for the educational vision especially the higher educational outlook..